Receive and Interpretation in the Literary Criticism - كاظم سهيل, ديلم; Natiq Alwan, Malath (Journal of College of Education, 2019)
The  Arabic language has  high status among all societies, of different cultural and affiliations , because, it is a key source of communications among members of society, thought which people express  their feeling and thoughts, moreover, the cultural heritage of nations is transferred, and among members of the same nation.Researchers in Arabic language have identified and displayed its treasures linguistic,, perhaps the terms "receiving and interpretation", among the terms have raised the interest of researchers and students, and we are among them", because the terms have an important and effective role in delivering the massage of the text maker in a clear and bright view, make the recipient feel with pleasure.We also, believed that these two terms are closely related to each other and include discrimination in clarifying the substance of the texts. Although, the term "receiving" is closer to the subject of literary criticism, while the term " interpretation" is closer to the Qur'anic knowledge, such as, Science of interpretation, Speech, Philosophy, and Fundamentals of Jurisprudence. Therefore, we focused of these two terms in our research.